The association of health behavioral risk factors with quality of life in northern Sweden : A cross-sectional survey - Al-Rubaye, Ali K. Q.; Johansson, Klara; Alrubaiy, Laith (Journal of General and Family Medicine, 2020)
Background: It is well known that behavioral risk factors such as obesity, smoking, physical activity, diet, and excessive alcohol are linked to general health in northern Sweden. This study aimed to explore the joint relationship between these risk factors and the quality of life (QoL). Methods: Data were collected from Sweden's national public health survey between February and May 2014 in the four northern counties in Sweden. QoL was assessed using the EuroQol (EQ‐5D). Multivariable regression analysis was used to examine the relationship between five risk factors: BMI, physical activity, smoking status, fruit and vegetable intake, and alcohol consumption and QoL. Results: Data from 17 138 complete questionnaires showed that individuals who were not obese, did at least 30 minutes of physical activity daily, consumed at least 3 portions of vegetable or fruits, were not smoking daily, and who did not report being drunk at least once every week were found to have better QoL (P < .005). The mean EQ‐5D score ranged from 0.85 to 0.79. Approximately, two thirds of the studied population reported being physically active for at least 30 minutes every day and two fifths of them had a normal BMI. Only around 7% of the sample reported that they were eating the recommended daily level of fruits and vegetables. Conclusions: The results of the study suggest that QoL has a significant relationship with lifestyle behaviors. This finding would emphasize the role of interventions to improve population health.